P.1.05 Developing a workplace intelligence system for exposure-control in great britain (WISE-GB). (April 2019) - Chen, Yiqun; Curran, Andrew
Abstract : The Health and Safety Executive (HSE) is a risk based regulator for workplace health and safety in GB. It has an intelligence-led operational approach. To inform HSE's risk control strategies, WISE-GB is developed to capture and integrate diverse but relevant data sources on an ongoing basis to generate intelligence, in a timely fashion, through enhanced analytic operation (i.e. statistical modelling, spatial and temporal analyses and expert interpretation) for monitoring and evaluation of the effectiveness of workplace exposure-control in GB. A workshop was organised in October 2017 to bring stakeholders across HSE to develop a common vision for WISE-GB and to identify the next steps for development. WISE-GB will generate national representative intelligence on the patterns (levels and distributions) of risk exposure to important hazards, which should support: 1) risk assessment, prioritisation and targeting risk control efforts; and 2) monitoring and evaluation of interventions, where reliable intelligence on improvement of exposure-control is critical in linking positive changes in attitude and behavioural about workplace exposures to better prevention of work-related ill health. A feasibility study will be presented, using Respirable Crystalline Silica (RCS) as an example, to illustrate WISE-GB development methods. This include: 1) capturing historical data as well as data gathered continuously through HSE operation and research, 2) accessing and utilisation inspection information, industry data, and data from other industrial countries to fill the potential data gaps; and 3) integrating diverse data sources to generate national representative intelligence. We will also demonstrate how the intelligence from WISE-GB contributes to the monitoring and evaluation of the HSE Health and Work programme on prevention of Occupational Lung Disease (OLD). These will help HSE towards developing a fit-for-purpose WISE-GB to generate real-time national picture of the effectiveness of exposure-control in GB workplaces. © British Crown copyright (2019)